SP Gas Well Development Strategy at Offshore B Flowstation Using Analytical Hierarchy Process - Septian Cahya; Nurhadi Siswanto (Institut Teknologi Sepuluh Nopember, 2020)
This research is focused on analyzing strategies for developing SP well production in the B Flowstation offshore platform. The development in question is the construction of platforms and SP gas well production facilities based on the application of the SP gas well production operation mode to the existing Bravo Flowstation production system. The application of the SP well production operation mode will determine the design of the production facility and the amount of investment the company has to operate the SP well. The mode of production operation also affects the continuity and stability of SP gas well production in meeting the company's production targets. Based on seismic results and studies from the company that wells have capacity of 53.5 BCF with a gas production rate of 30 MMSCFD and is capable of producing for 6 years. Incorrect application of operating modes has the potential to cause premature production, which means that production from the well cannot last for 6 years. That is because the occurrence of water coning which has an impact on gas production is hindered by the rate of water production. In addition, the application of the operation mode also affects the continuity of gas well production. Gas production activities may be halted due to production shutdowns due to a mismatch of the SP well production line technology design that is applied to an existing production system. The cessation of SP well gas production activities can also be caused by operational activities such as maintenance activities. From the potential problems that arise, a qualitative analysis is needed by considering every aspect of the problem. With the complexity of things that must be considered in the production development strategy used the AHP (Analytic Hierarchy Process) method. 4 alternative choices of SP well operation modes are determined by the expert. The alternatives include: high pressure mode; low pressure mode; medium pressure mode; and combine high low pressure mode. Criteria identified by the expert include: technology; capital costs; the impact of existing production; operating costs; decline reservoir. From the data obtained in the field as a reference for experts to determine the weighting in the AHP method, the dominant alternative is the development of SP wells based on the combining high low pressure operation mode. The high low pressure operating mode provides continuous production without being affected by existing production processes and has the potential for a medium for water coning. With a sizeable investment the SP well development strategy can be on target in production and on return on investment.